2019
DOI: 10.1039/c9cp04504j
|View full text |Cite
|
Sign up to set email alerts
|

Rapid carbene formation increases ion diffusivity in an imidazolium acetate ionic liquid confined between polar glass plates

Abstract: 1-Ethyl-3-methyl-imidazolium acetate ([EMIM][OAc]) is one of the most widely used ionic liquids for various applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Again this may be due to the presence of impurities, as discussed above. In this regard, it may be noted that Filippov et al have reported the formation of volatile decomposition products of 1-ethylimidazoliumacetate ([EMIM]­[Ac]) catalyzed by polar glass plates that could be removed under vacuum. These products significantly increased the ion self-diffusion coefficients, corresponding to a proportionate decrease in the viscosity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Again this may be due to the presence of impurities, as discussed above. In this regard, it may be noted that Filippov et al have reported the formation of volatile decomposition products of 1-ethylimidazoliumacetate ([EMIM]­[Ac]) catalyzed by polar glass plates that could be removed under vacuum. These products significantly increased the ion self-diffusion coefficients, corresponding to a proportionate decrease in the viscosity.…”
Section: Discussionmentioning
confidence: 99%
“…Again this may be due to the presence of impurities, as discussed above. In this regard, it may be noted that Filippov et al 44…”
Section: Journal Ofmentioning
confidence: 96%
“…Therefore, for the first time, we investigated the TE properties by combining PEO with Emim:OAC, considering that the cations diffusivity of Emim:OAC is higher than that of anions and PEO is able to promote cation transport. [20] Figure 1a presents the S i of PEO-Emim:OAC ionogels with different IL content. We can see that the S i increases significantly with increasing the weight percentage of Emim:OAC (W IL /W PEO+IL ), from S i = 8 mV K −1 for W IL /W PEO+IL = 50% to S i = 13.6 mV K −1 for W IL /W PEO+IL = 80%, which are higher than that of pristine Emim:OAC (2 mV K −1 shown in Figure S1 in the Supporting Information) and PEO (2.99 mV K −1 reported [14] ).…”
Section: Design Principle and Te Properties Of Peo-il Ionogelsmentioning
confidence: 99%
“…This, in fact, seems likely as carbenes are known to form transiently in imidazolium acetate ionic liquids under certain conditions. [198][199][200] While these structures may be stable at room temperature, the reactions are often carried out at elevated temperatures, either due to deliberate external heating or due to the liberation of reaction heat. The thermal stability of the ionic liquids is drastically reduced by the presence of the amino group, in particular for the less nucleophilic anions.…”
Section: Brønsted Basic Ionic Liquidsmentioning
confidence: 99%
“…In dialkylimidazolium acetate ionic liquids, carbenes can exist at elevated temperatures or in the presence of glass or metal surfaces, as evidenced by changes in NMR spectra and theoretical calculations. [198][199][200] In the bulk ionic liquid phase, carbene formation is insignificant at ambient temperatures.…”
Section: Brønsted Basic Ionic Liquidsmentioning
confidence: 99%